A novel non-catalytic plasmonic immunoabsorbant assay amplification mechanism - Aditya Saran; Shuai Hou; Yinglu Ji (Nano Trends)
The amplification of signals is dependent upon enzyme/ catalyst. Enzyme activity, specificity, pH condition, enzyme linkers, stability, storage and efficiency are some very important factors that can eventually affect the detection results. We aimed to amplify signals without the assistance of enzyme/ catalyst so that the strategy can be used in the wide range of signal detection including immune-assay. Silver nanocrystals (Ag NCs) grown from self-nucleation are used as chromogens due to their strong plasmon band at ∼ 400 nm. During 140 s of reaction time in presence of 6.10 mM CTAB and 0.61 mM of AgNO3, the 0.57 mM of Ascorbic acid allows Ag over growth on antibody-tagged gold nanospheres (10±0.5 nm) that competes silver atoms from the self-nucleation growth and thus affects the growth kinetics of the latter. By utilizing the opened kinetic window, sensitive detection has been achieved from 6.67 × 10–14 M (1 pg) to 3.33 × 10–9 M (50 ng) using human IgG as a model protein. The non-catalytic plasmonic immunoabsorbant assay we developed herein adds a new possibility of plasmonic NPs for sensitive detection. The detection slope and resolution is higher and better than those via signal amplification through the assistance of enzymes/ catalysts. This work supports the concept that nanoparticles mediated reactions are sensitive enough that they have the potential to go independently without enzymes/ catalyst assistance.